Preparation method and application of MXene / PVA / SBR rubber composite material with underwater low-frequency sound absorption performance
Patent Information
- Application Number
- CN202410709427.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-03
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2044-06-03
AI Technical Summary
[0004]MXene作为新兴的二维材料家族,具有层状结构、表面官能团丰富,便于组装形成多样化的微观结构,并可采用多种工艺加工成自支撑薄膜,因此将其与具有粘弹性的橡胶复合,可望突破传统的水声材料吸声机理的限制,提高低频吸声性能,目前国内外还未有相关研究和报道
[0034]本发明通过设计制备MXene,再采用PVA插层MXene,经抽滤沉积后制备MXene/PVA薄膜,最后通过层压方式与SBR橡胶进行复合,制备MXene/PVA/SBR橡胶复合材料。有望克服传统的水声材料吸声机理的限制,提高水下低频声波的吸声性能,解决了低频吸声的难题,在0.4~7.0kHz范围内的平均吸声系数为0.81,其中在0.4~1.2kHz范围内为0.60,在1.2~7.0kHz范围内为0.86。
Smart Images

Figure CN118664937B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of underwater sound-absorbing materials technology, and more particularly to a method for preparing and applying an MXene / PVA / SBR rubber composite material with underwater low-frequency sound absorption properties. Background Technology
[0002] Underwater sound-absorbing materials can absorb sound waves in water and convert them into other forms of energy. They can effectively reduce underwater noise, decrease target sonar signals, and improve the performance of acoustic equipment. They are widely used in constructing anechoic pools, laying anechoic tiles on submarines, and processing sonar signals, and are of great significance to marine scientific research and defense equipment manufacturing.
[0003] Common underwater sound-absorbing materials include rubber composites, metal composites, and acoustic pressure ceramics. Among them, rubber composites have been widely used due to their excellent impedance matching characteristics and relatively low cost. However, with the rapid development of low-frequency sonar technology, more stringent requirements have been placed on the performance of underwater sound-absorbing materials in the low-frequency range. Because low-frequency sound waves have longer wavelengths, lower energy densities, and significant diffraction effects, traditional rubber composites are insufficient to meet the low-frequency sound absorption requirements. Therefore, developing a novel rubber composite material to achieve efficient low-frequency sound absorption has become an important research topic in this field.
[0004] MXene, as an emerging family of two-dimensional materials, possesses a layered structure and abundant surface functional groups, facilitating the assembly into diverse microstructures. It can also be processed into self-supporting thin films using various techniques. Therefore, combining MXene with viscoelastic rubber holds promise for overcoming the limitations of traditional underwater acoustic material absorption mechanisms and improving low-frequency sound absorption performance. Currently, there are no relevant studies or reports both domestically and internationally. Thus, developing MXene-rubber composites holds immense potential and promising prospects for solving the problem of underwater low-frequency sound absorption. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing and applying an MXene / PVA / SBR rubber composite material with underwater low-frequency sound absorption properties.
[0006] First, an MXene nanoparticle colloidal solution is prepared. Then, an MXene / PVA film is prepared by intercalating MXene with PVA, and this film is used as a sound-absorbing unit. It is then composited with SBR rubber to prepare an MXene / PVA / SBR rubber composite material. Compared with common underwater sound-absorbing rubbers, the MXene / PVA / SBR rubber composite material combines the viscoelasticity of SBR rubber with the unique layered structure and properties of two-dimensional MXene, potentially overcoming the limitations of traditional underwater acoustic material absorption mechanisms and achieving absorption of low-frequency sound waves in a small size. Furthermore, the MXene / PVA film requires no complex processing; the composite material is prepared by lamination with rubber, making the entire preparation process simple, flexible, and easy to adjust the performance parameters of the composite material. The MXene / PVA / SBR rubber composite material prepared by the method of this invention can be used as an underwater low-frequency sound-absorbing material in marine scientific research, defense equipment manufacturing, and other fields.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows:
[0008] This invention provides a method for preparing an MXene / PVA / SBR rubber composite material with underwater low-frequency sound absorption properties, the method comprising the following steps:
[0009] (a) The MAX phase powder was chemically etched, and after centrifugation, it was repeatedly washed and centrifuged, and then ultrasonicated and centrifuged to obtain an MXene colloidal solution;
[0010] (b) Preparation of non-crosslinked MXene / PVA films and crosslinked MXene / PVA films;
[0011] The preparation method of the non-crosslinked MXene / PVA film is as follows: PVA is fully dissolved in deionized water and then added to MXene colloidal solution. After sonication, a mixed solution is obtained. The mixed solution is filtered through a vacuum-assisted filtration device, and the filtered product is dried to obtain the non-crosslinked MXene / PVA film.
[0012] The preparation method of the cross-linked MXene / PVA film is as follows: PVA is fully dissolved in deionized water and then added to MXene colloidal solution. After sonication, a mixed solution is obtained. The mixed solution is chemically cross-linked with aldehydes and then filtered through a vacuum-assisted filtration device. The filtered product is dried to obtain the cross-linked MXene / PVA film.
[0013] (c) On a flat vulcanizing machine, the compound rubber is vulcanized in the mold in the first stage to prepare SBR rubber vulcanized sheet. Then, the SBR rubber vulcanized sheet and MXene / PVA film on both sides are stacked and placed in the mold. The second stage of vulcanization is carried out on the vulcanizing machine to obtain MXene / PVA / SBR rubber composite material.
[0014] In the above technical solution, further, in step (a), the etching solution used for chemical etching is a mixed solution of hydrochloric acid and lithium fluoride, the mass ratio of hydrochloric acid to lithium fluoride is 1 to 5:1, preferably 3 to 4:1; the mass ratio of lithium fluoride to MAX phase powder is 1 to 10:1, preferably 2 to 5:1; the temperature of chemical etching is 15 to 45°C, and the time is 12 to 72 hours.
[0015] In the above technical solution, further, in step (a), the general chemical formula of the MAX phase powder is M n+1 AX n Where M is a transition metal element, A is a group IIIA or IVA element, X is C or N, n = 1, 2, 3, and is further preferably one of Ti2AlC, Ti3AlC2, Cr2AlC, V2AlC, Mo2AlC, Nb2AlC and Ta2AlC;
[0016] The general chemical formula of MXene is M n+1 X n T x Where M is a transition metal element, X is a C or N element, and T x Its surface functional groups are selected from -OH, -O, -Cl and -F, n = 1, 2, 3, and more preferably Ti2CT. x Ti3C2T x Cr2CT x V2CT x Mo2CT x Nb2CT x and Ta2CT x One of them.
[0017] In the above technical solution, further, in step (a), the centrifugation speed is 500-10000 rpm and the time is 0.1-4h;
[0018] The duration of the ultrasound is 0.1 to 3 hours.
[0019] In the above technical solution, further, in step (b), the mass ratio of MXene to PVA in the MXene colloidal solution is 1.5 to 15:1, preferably 2.0 to 10:1;
[0020] The molecular weight of the PVA is 3,000 to 300,000, preferably 89,000 to 98,000.
[0021] In the above technical solution, further, in step (b), the thickness of the MXene / PVA film is 5 to 50 μm, preferably 20 to 40 μm.
[0022] In the above technical solution, further, in step (b), the ultrasound time is 5 to 10 minutes.
[0023] In the above technical solution, further, in step (b), the aldehyde is a dialdehyde or a polyaldehyde, preferably glutaraldehyde; the mass ratio of Mxene to the mass of the aldehyde in the MXene colloidal solution is 5 to 15.
[0024] The chemical crosslinking reaction temperature is 40–90°C, preferably 50–70°C, and the reaction time is 1–24 h.
[0025] Furthermore, in step (b), the shape of the MXene / PVA film can be cut as needed, preferably in the form of a circle, ellipse, triangle, square, trapezoid, star, or a variation thereof.
[0026] In the above technical solution, further, in step (c), the preparation method of the compound is as follows: raw materials with a mass ratio of SBR rubber raw rubber: carbon black: sulfur: accelerator TBBS: stearic acid: zinc oxide = 100:50:1.75:1:1:3 are mixed in a two-roll mill for 10 to 300 minutes and 2 to 10 thin passes to obtain the compound;
[0027] The raw SBR rubber is emulsion SBR rubber or solution SBR rubber.
[0028] The mixing time is 10 to 300 minutes, preferably 30 to 90 minutes;
[0029] The number of thin-pass tests is 2 to 10, preferably 3 to 6.
[0030] In the above technical solution, further, in step (c), the conditions for the first stage of vulcanization are: temperature of 140-170℃, preferably 155℃-165℃, pressure of pre-compression of 3-10MPa, preferably 7-9MPa, time of 1-30min, preferably 1-10min, followed by pressure increase of 6-15MPa, preferably 11-13MPa, and time of 3-150min; the conditions for the second stage of vulcanization are: temperature of 140-170℃, preferably 155℃-165℃, pressure of 6-15MPa, and time of 4-180min, preferably 10-30min.
[0031] In the above technical solution, further, in step (c), the MXene / PVA film is a non-crosslinked MXene / PVA film, a crosslinked MXene / PVA film, or a combination of non-crosslinked and crosslinked MXene / PVA films.
[0032] Another aspect of the present invention provides an application of the MXene / PVA / SBR rubber composite material prepared by the above-mentioned preparation method as an underwater sound-absorbing material.
[0033] The beneficial effects of this invention are as follows:
[0034] This invention designs and prepares MXene, then intercalates MXene with PVA, and prepares an MXene / PVA thin film through filtration deposition. Finally, it is laminated with SBR rubber to prepare an MXene / PVA / SBR rubber composite material. This is expected to overcome the limitations of traditional underwater acoustic material sound absorption mechanisms, improve the sound absorption performance of low-frequency underwater sound waves, and solve the problem of low-frequency sound absorption. The average sound absorption coefficient is 0.81 in the range of 0.4–7.0 kHz, with 0.60 in the range of 0.4–1.2 kHz and 0.86 in the range of 1.2–7.0 kHz.
[0035] The preparation process of this invention is simple and has broad application prospects in fields such as marine scientific research and defense equipment manufacturing. Attached Figure Description
[0036] Figure 1 This is a scanning electron microscope image of the cross-section of the MXene / PVA thin film used in Example 1;
[0037] Figure 2 The sound absorption coefficient curve of the MXene / PVA film composite sound-absorbing adhesive used in Example 1 is shown. Detailed Implementation
[0038] The following non-limiting embodiments are intended to enable those skilled in the art to more fully understand the present invention, but do not limit the invention in any way.
[0039] Example 1
[0040] (a) In a reaction vessel, hydrochloric acid and lithium fluoride were mixed to prepare an acidic etching solution at a mass ratio of 4. 2 g of Ti3AlC2 powder was gradually added to the etching solution to etch Ti3C2T. x The solution was used for etching at a temperature of 35°C for 48 hours to etch Ti3C2T. xThe solution was transferred to centrifuge tubes and centrifuged. The resulting precipitate was washed with deionized water and centrifuged again. This step was repeated until the pH of the supernatant was close to 7 and the color turned black. During centrifugation, the speed was controlled at 3500 rpm and the time was 5 min per cycle. The centrifuge tubes were then placed in an ultrasonic disperser and sonicated for 1 h. Finally, the supernatant was collected by centrifugation to obtain Ti3C2T. x Colloidal solutions;
[0041] (b) Dissolve PVA with a molecular weight of 89,000–98,000 in deionized water at 60°C to a mass fraction of 0.2 wt%. Then, slowly add 40 ml of the PVA solution to 400 ml of Ti3C2T solution with a concentration of 1.5 mg / ml. x In the colloidal solution, the mass ratio of MXene to PVA in the mixed solution was 7.5:1. After further dispersion in an ultrasonic disperser for 5 minutes, 40 ml was taken and filtered through a vacuum-assisted filtration device. The filtered product was dried to form a non-crosslinked Ti3C2T with a thickness of 25 μm. x / PVA film;
[0042] (c) Mix 100g of emulsion-polymerized SBR1500E, 50g of carbon black, 1.75g of sulfur, 1g of accelerator TBBS, 1g of stearic acid, and 3g of zinc oxide in a two-roll mill for 30 minutes, passing through a thin pass 3 times to obtain a compound. Take 3g of the compound and test its vulcanization curve in a rotorless vulcanizer at 160℃ to determine the vulcanization process parameters. On a flat vulcanizer, firstly, place 12g of the compound in a circular mold with a diameter of 12cm and a thickness of 1mm for the first stage. SBR rubber vulcanizates were prepared by vulcanization. Then, a vulcanizate with SBR rubber on both sides and an MXene / PVA film on the inner side was placed in a circular mold with a diameter of 12 cm and a thickness of 10 mm for a second-stage vulcanization. The vulcanization conditions were as follows: the vulcanization temperature for both stages was 160℃; the first stage vulcanization was pre-pressurized at 8 MPa for 2 minutes, followed by an increase in pressure to 12 MPa for 8 minutes; the second stage vulcanization did not require pre-pressurization and was directly vulcanized at 12 MPa for 10 minutes to obtain Ti3C2T. x / PVA / SBR rubber composite material.
[0043] Acoustic test sample preparation and testing:
[0044] First, the MXene / PVA / SBR rubber vulcanizate sample was bonded to a circular steel backing. Then, the underwater sound absorption performance was tested using an underwater acoustic standing wave tube acoustic system. The test frequency range was 0.4 to 7.0 kHz. The sound absorption data in the 0.4 to 4.0 kHz band were obtained using the standing wave method, and the data in the 4.0 to 7.0 kHz band were obtained using the pulse method.
[0045] Figure 1 The Ti3C2T used in this embodiment x The scanning electron microscope image of the cross section of the PVA film shows that the film has a two-dimensional layered structure, which is beneficial to the loss of sound energy.
[0046] Figure 2 The non-crosslinked Ti3C2T used in this embodiment x The sound absorption coefficient curve of the PVA film composite sound-absorbing rubber shows the following results:
[0047] Two SBR vulcanized films and one non-crosslinked Ti3C2T film were used. x PVA films are alternately arranged on the mold and laminated with one layer of film. The average sound absorption coefficient is 0.31 in the low frequency sound wave range of 0.4 to 1.2 kHz and the average sound absorption coefficient is 0.82 in the frequency sound wave range of 1.2 to 7.0 kHz.
[0048] Five SBR vulcanized films and four non-crosslinked Ti3C2T films were used. x PVA films are alternately arranged on the mold, and four layers of film are laminated. The average sound absorption coefficient is 0.32 in the low frequency sound wave range of 0.4 to 1.2 kHz, and the average sound absorption coefficient is 0.93 in the frequency sound wave range of 1.2 to 7.0 kHz.
[0049] Ten SBR vulcanized films and nine non-crosslinked Ti3C2T films were used. x The PVA films are alternately arranged on the mold, and nine layers of film are laminated. The average sound absorption coefficient is 0.60 in the low frequency sound wave range of 0.4 to 1.2 kHz, and the average sound absorption coefficient is 0.86 in the frequency sound wave range of 1.2 to 7.0 kHz.
[0050] Therefore, it can be seen that Ti3C2T x PVA / SBR rubber composites exhibit excellent low-frequency sound absorption properties. Increasing the number of film layers significantly improves the sound absorption coefficient in the 0.4–1.2 kHz frequency range, while initially increasing and then slightly decreasing in the 1.2–7.0 kHz low-frequency range.
[0051] Example 2
[0052] The preparation and testing methods of the MXene / PVA / SBR rubber composite material are similar to those in Example 1, except that the MAX phase powder used is Ti2AlC and the number of laminated films is 9.
[0053] The test results showed that the sample had an average sound absorption coefficient of 0.41 in the 0.4–1.2 kHz frequency range and an average sound absorption coefficient of 0.53 in the 1.2–7.0 kHz frequency range.
[0054] Example 3
[0055] The preparation and testing methods of the MXene / PVA / SBR rubber composite material are similar to those in Example 1, except that the MAX phase powder used is Gr3AlC2 and the number of laminated films is 9.
[0056] The test results showed that the sample had an average sound absorption coefficient of 0.32 in the sound wave range of 0.4 to 1.2 kHz and an average sound absorption coefficient of 0.57 in the sound wave range of 1.2 to 7.0 kHz.
[0057] Example 4
[0058] The preparation and testing methods of the MXene / PVA / SBR rubber composite material are similar to those in Example 1, except that the molecular weight of the PVA used is 68,000 and the number of laminated films is 9.
[0059] Through testing, the sample showed an average sound absorption coefficient of 0.42 in the 0.4–1.2 kHz frequency range and an average sound absorption coefficient of 0.61 in the 1.2–7.0 kHz frequency range.
[0060] Example 5
[0061] The preparation and testing methods of the MXene / PVA / SBR rubber composite material are similar to those in Example 1, except that the mass fraction of PVA used is 0.5 wt%, the mass ratio of MXene to PVA is 3:1, and the number of laminated films is 9.
[0062] The test results showed that the sample had an average sound absorption coefficient of 0.40 in the frequency range of 0.4 to 1.2 kHz and an average sound absorption coefficient of 0.60 in the frequency range of 1.2 to 7.0 kHz.
[0063] Example 6
[0064] The preparation and testing methods of the MXene / PVA / SBR rubber composite material are similar to those in Example 1, except that the mass fraction of the PVA solution is 1.0 wt%, the mass ratio of MXene to PVA is 1.5:1, and the number of laminated films is 9.
[0065] The test results showed that the sample had an average sound absorption coefficient of 0.31 in the frequency range of 0.4 to 1.2 kHz and an average sound absorption coefficient of 0.72 in the frequency range of 1.2 to 7.0 kHz.
[0066] Example 7
[0067] The preparation and testing methods of the MXene / PVA / SBR rubber composite material are similar to those in Example 1, except that the concentration of the MXene colloidal solution is 3 mg / ml, the mass ratio of MXene to PVA is 15:1, and the number of laminated films is 9.
[0068] The test results showed that the sample had an average sound absorption coefficient of 0.28 in the frequency range of 0.4 to 1.2 kHz and an average sound absorption coefficient of 0.66 in the frequency range of 1.2 to 7.0 kHz.
[0069] Example 8
[0070] The preparation and testing methods of the MXene / PVA / SBR rubber composite material are similar to those in Example 1, except that the film thickness is 45 μm and the number of laminated films is 9.
[0071] The test results showed that the sample had an average sound absorption coefficient of 0.41 in the 0.4–1.2 kHz frequency range and an average sound absorption coefficient of 0.62 in the 1.2–7.0 kHz frequency range.
[0072] Example 9
[0073] Ti3C2T x The preparation and testing methods for the PVA / styrene-butadiene rubber composite material are similar to those in Example 1, except that a cross-linked Ti3C2T cross-linked Ti3C2T cross-linked composite material is used. x / PVA film, and the number of laminated films is 1 layer.
[0074] The test results showed that the sample had an average sound absorption coefficient of 0.51 in the frequency range of 0.4 to 1.2 kHz and an average sound absorption coefficient of 0.91 in the frequency range of 1.2 to 7.0 kHz.
[0075] The above-mentioned cross-linked Ti3C2T x The preparation method of PVA thin film is as follows:
[0076] First, prepare an MXene / PVA mixed solution.
[0077] (a) Dissolve PVA with a molecular weight of 89,000–98,000 in deionized water at 60°C until the mass fraction is 0.2 wt%. Take 40 ml of the PVA solution and slowly add it to 400 ml of Ti3C2T solution with a concentration of 1.5 mg / ml. x In the colloidal solution, a mixed solution of MXene / PVA was obtained;
[0078] (2) Transfer the MXene / PVA mixed solution to a flask and add 0.08 ml of glutaraldehyde for chemical cross-linking. The cross-linking reaction is carried out under a nitrogen atmosphere for 2 hours and at a temperature of 80°C.
[0079] (3) After the cross-linking reaction is completed, 40 ml of the solution is taken and filtered through a vacuum-assisted filtration device. The filtered product is dried to obtain a cross-linked MXene / PVA film.
[0080] Example 10
[0081] The preparation and testing methods of the MXene / PVA / SBR rubber composite material are similar to those in Example 1, except that vulcanized sheets are prepared using emulsion SBR rubber SBR1502E, and the number of laminated films is 9.
[0082] The test results showed that the sample had an average sound absorption coefficient of 0.54 in the sound wave frequency range of 0.4 to 1.2 kHz and an average sound absorption coefficient of 0.82 in the sound wave frequency range of 1.2 to 7.0 kHz.
[0083] Example 11
[0084] The preparation and testing methods of the MXene / PVA / SBR rubber composite material are similar to those in Example 1, except that solution polymerized SBR rubber is used to prepare vulcanized sheets and the number of laminated films is 9.
[0085] The test results showed that the sample had an average sound absorption coefficient of 0.52 in the frequency range of 0.4 to 1.2 kHz and an average sound absorption coefficient of 0.87 in the frequency range of 1.2 to 7.0 kHz.
[0086] Example 12
[0087] The preparation and testing methods of the MXene / PVA / SBR rubber composite material are similar to those in Example 1, except that the shape of the MXene / PVA film is different. A square film with a side length of 3cm is used, and the number of laminated films is 9.
[0088] The test results showed that the average sound absorption coefficient of the sample was 0.31 in the frequency range of 0.4 to 1.2 kHz and 0.71 in the frequency range of 1.2 to 7.0 kHz.
[0089] Comparative Example 1
[0090] The preparation of SBR rubber material differs from Example 1 in that Ti3C2T is not used. x The SBR rubber material was prepared by laminating a PVA film with an SBR rubber film according to the method in Example 1, using 10 SBR vulcanized sheets directly laminated to obtain the SBR rubber material.
[0091] Through testing, it was determined that the average sound absorption coefficient of the pure rubber vulcanizate sample was 0.04 in the frequency range of 0.4 to 1.2 kHz and 0.42 in the frequency range of 1.2 to 7.0 kHz, indicating a very low sound absorption coefficient.
[0092] Comparative Example 2
[0093] Rubber composite materials were prepared according to the method in Example 1, except that pure Ti3C2T was used. x The film, the number of laminated films is 9.
[0094] The test results showed that the sample had an average sound absorption coefficient of 0.18 in the 0.4–1.2 kHz frequency range and an average sound absorption coefficient of 0.46 in the 1.2–7.0 kHz frequency range, which is very low.
[0095] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
[0096] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A method for preparing an MXene / PVA / SBR rubber composite material with underwater low-frequency sound absorption properties, characterized in that, The method includes the following steps: (a) Preparation of MXene colloidal solution; The preparation method of the MXene colloidal solution is as follows: chemically etch the MAX phase powder, wash and centrifuge repeatedly after centrifugation, and then obtain the MXene colloidal solution by ultrasonic peeling and centrifugation. (b) Preparation of non-crosslinked MXene / PVA films and crosslinked MXene / PVA films; The preparation method of the non-crosslinked MXene / PVA film is as follows: PVA is fully dissolved in deionized water and then added to MXene colloidal solution. After sonication, a mixed solution is obtained. The mixed solution is filtered through a vacuum-assisted filtration device, and the filtered product is dried to obtain the non-crosslinked MXene / PVA film. The preparation method of the cross-linked MXene / PVA film is as follows: PVA is fully dissolved in deionized water and then added to MXene colloidal solution. After sonication, a mixed solution is obtained. The mixed solution is chemically cross-linked with aldehydes and then filtered through a vacuum-assisted filtration device. The filtered product is dried to obtain the cross-linked MXene / PVA film. (c) Preparation of MXene / PVA / SBR rubber composite material; The preparation method of the MXene / PVA / SBR rubber composite material is as follows: on a flat vulcanizing machine, the compound rubber is vulcanized in a mold in the first stage to prepare SBR rubber vulcanized sheet. Then, the SBR rubber vulcanized sheet is placed on both sides and the MXene / PVA film is placed on the inside. After stacking, it is placed in a mold and vulcanized in the second stage on the vulcanizing machine to obtain the MXene / PVA / SBR rubber composite material. The MXene / PVA film is a non-crosslinked MXene / PVA film, a crosslinked MXene / PVA film, or a combination of non-crosslinked and crosslinked MXene / PVA films.
2. The preparation method according to claim 1, characterized in that, In step (a), the general chemical formula of the MAX phase powder is M n+1 AX n Where M is a transition metal element, A is a group IIIA or IVA element, X is C or N, and n=1, 2, 3; The general chemical formula of MXene is M n+1 X n T x Where M is a transition metal element, X is a C or N element, and T x Its surface functional groups are selected from one of -OH, -O, -Cl and -F, n=1, 2, 3.
3. The preparation method according to claim 1, characterized in that, In step (b), the mass ratio of MXene to PVA in the MXene colloidal solution is 1.5 to 15:1; The molecular weight of the PVA is 3,000 to 300,000.
4. The preparation method according to claim 1, characterized in that, In step (b), the thickness of the MXene / PVA film is 5~50μm.
5. The preparation method according to claim 1, characterized in that, In step (b), the aldehyde is a dialdehyde or a polyaldehyde; the reaction temperature for the chemical crosslinking is 40~90℃, and the reaction time is 1~24h.
6. The preparation method according to claim 1, characterized in that, In step (c), the preparation method of the compound is as follows: raw materials with a mass ratio of SBR rubber raw rubber: carbon black: sulfur: accelerator TBBS: stearic acid: zinc oxide = 100:50:1.75:1:1:3 are mixed in a two-roll mill for 10~300 min and 2~10 thin passes to obtain the compound; The raw SBR rubber is emulsion SBR rubber or solution SBR rubber. The mixing time is 10~300min; The number of thin-pass tests is 2 to 10.
7. The preparation method according to claim 1, characterized in that, In step (c), the conditions for the first stage of vulcanization are: temperature of 140~170℃, pressure of pre-compression of 3~10MPa for 1~30min, and then pressure of 6~15MPa for 3~150min. The conditions for the second stage of vulcanization are: temperature of 140~170℃, pressure of 6~15MPa, and time of 4~180min.
8. The application of an MXene / PVA / SBR rubber composite material prepared by any one of claims 1-7 as an underwater sound-absorbing material.
Citation Information
Patent Citations
Aerogel with high electromagnetic shielding and high electromagnetic absorption performance and integrated preparation method thereof
CN116640353A
Honeycomb sandwich structure high-temperature-resistant broadband wave-absorbing composite material based on Ti3C2Tx MXene aerogel and preparation method of honeycomb sandwich structure high-temperature-resistant broadband wave-absorbing composite material
CN116811376A